O osobliwościach dyskursów w edukacji - Nawrocki, Radosław (Studia Edukacyjne, 2018)
The basic goal of the text is to follow the work strategy on selected pedagogical concepts as part of educational discourses. I assume that within the framework of the functioning of discursive practices in education, a certain work is done, which flattens the conceptual grid regarding education. Thus, these concepts are unambiguous, boil down to the most direct, superficial and obvious meaning. The way of thinking about education, present in the dominant discourses located in the social circulation, causes that educational processes are devoid of meaning wealth. This is how it sets the playing field in thinking about education, designing educational policy and educational practice. The treatment, which is to restore the educational discourses to depth, aporethism, internal struggle, the element of contradiction is to launch a specific etymological work that reveals the fuller meaning of the basic concepts that build the educational imagination. Thanks to this, a certain contrast will also be created between the extracted meaning and those meanings that are promoted in the most varied discursive practices launched in the field of education